Digital Storytelling in Islamic Religious Education: Enhancing Engagement and Identity Formation in Contemporary Pedagogical Contexts - Inayah Inayah; Moh Ali; Ade Hidayat; Taqiyuddin Tqiyuddin (Yayasan Adra Karima Hubbi, 2026)
Background. Islamic religious education has long struggled to bridge the gap between traditional transmissive pedagogical approaches and the experiential, identity-forming needs of contemporary Muslim learners in digitally saturated environments. Purpose. This study examines how digital storytelling integration into Islamic religious education enhances student engagement and Islamic identity formation among secondary school students in Indonesia. Method. A sequential explanatory mixed-methods design was employed, combining a quasi-experimental pre-test/post-test control group structure with phenomenological case study inquiry. Purposive cluster sampling yielded 240 student participants across four madrasah institutions, with 24 participants selected for qualitative inquiry. Results. ANCOVA results revealed statistically significant treatment effects on both engagement (F(1,237) = 128.64, p < .001, partial n2 = .353, Cohen’s d = 1.87) and Islamic identity formation (F(1,237) = 136.97, p < .001, partial n2 = .366, Cohen’s d = 1.94). Qualitative findings identified four thematic mechanisms: narrative ownership, emotional resonance, critical values engagement, and digital identity expression. Conclusion. Digital storytelling activates emotional and moral dimensions of Islamic formation more powerfully than conventional instruction, offering Islamic educators a theoretically grounded, empirically validated pedagogical framework for cultivating authentic religious engagement and coherent Islamic identity in contemporary learners.